Information technology protection and homeland security - Spellman, Frank R. (Homeland security series (Lanham, Md.), 2019)
The eleventh volume of a highly acclaimed series on critical infrastructure and homeland security, Information Technology Protection and Homeland Security is an eye-opening account of a complex sector. This book describes the processes needed to identify assets, assess risk, implement protective programs, and measure their effectiveness.